Body Image as Well as Eating Disorder and Body Dysmorphic Disorder Symptoms in Heterosexual, Homosexual, and Bisexual Women - Henn, Alina T.; Taube, Christoph O.; Vocks, Silja; Hartmann, Andrea S. (Frontiers in Psychiatry, 2019)
Body image disturbance is a core symptom of eating disorders (ED) and body dysmorphic disorder (BDD). There is first evidence that females’ body image differs depending on sexual orientation, with heterosexual women (HEW) appearing to show more body image disturbance symptoms than homosexual women (HOW). Such disparities might be moderated by everyday discrimination experiences and involvement with the lesbian community. However, to date, there has been no comprehensive assessment of a broad range of body image facets such as drive for thinness, leanness and muscularity, body avoidance, body checking and body dissatisfaction, and ED and BDD pathology as well as moderating factors. Moreover, studies have often neglected bisexual women (BIW). A total of N=617 women (n=180 HOW, n=322 HEW, n=115 BIW) completed an online survey assessing the various facets of body image, ED and BDD pathology, discrimination experiences, and involvement with the lesbian community. Significant group differences were found regarding drive for leanness, body checking, investment behavior, and body ideal (all p<.05). BIW showed significantly more body checking than HOW. Compared to HEW, HOW reported a significantly lower drive for leanness and less investment behavior. HOW and BIW preferred a body ideal with significantly more body fat than did HEW (all p<.05). In contrast, no differences emerged in body dissatisfaction, drive for thinness and muscularity, body-related avoidance, ED and BDD pathology, and body image disturbance (all p>.05). In all groups, discrimination experiences were positively related to ED and BDD pathology and to body image disturbance (all p<.05); however, discrimination was significantly correlated with more body image facets in HEW than in HOW or BIW. Involvement with the lesbian community was positively correlated with a larger ideal body size in HOW (p<.05) and negatively correlated with drive for muscularity in BIW (p<.05). Despite the group differences in several body image facets, we found no consistent evidence of increased vulnerability to body image disturbance or associated pathology depending on sexual orientation. However, in HEW, discrimination experience might pose a risk factor for the development of body image-related pathology and single facets of body image disturbance.